Pengaruh Perbedaan Kepadatan Packing Induk Udang Vaname (Litopenaeus vanamei) Terhadap Tingkat Kelangsungan Hidup Dalam 12 Jam Pengiriman (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
Vannamei shrimp (Litopenaeus vannamei) is one of the most important aquaculture commodities with high economic value and strong market demand. The transportation of broodstock shrimp is a critical stage that may affect survival due to decreased oxygen levels and water quality deterioration. High stocking density during transportation can accelerate oxygen depletion and increase metabolic waste, leading to higher mortality. This study aimed to determine the effect of different packing densities on the survival rate of broodstock shrimp during 12 hours of transportation. The experiment used four treatments with densities of 6, 8, 10, and 12 shrimp per bag, each with six replications. Observed parameters included temperature, dissolved oxygen (DO), and survival rate. The results showed that lower stocking density produced higher survival rates, with the best result obtained at 6 shrimp per bag. Water quality remained within acceptable limits, although oxygen levels decreased with increasing density. Therefore, proper stocking density is essential to maintain shrimp survival during transportation.